A climatological dataset of nutrient, chlorophyll, and particulate matter distributions on the Ross Sea continental shelf derived from cruise-based measurements spanning 1967 to 2016 - Smith, Walker O., Jr.; Kaufman, Daniel E. (W&M ScholarWorks, 2018)
This dataset includes data used in the publication Smith and Kaufman (2018), Progress in Oceanography, which examines the temporal and spatial distributions of nutrients and particulate matter in the Ross Sea continental Shelf using cruise-based observations, and compares the resulting annual productivity estimates with previously reported satellite-based estimates. Specifically, these data represent distributions of nutrients, chlorophyll, particulate organic carbon, particulate organic nitrogen, and biogenic silica that were compiled from 42 cruises (from 1967 - 2016) to the Ross Sea continental shelf to generate a comprehensive climatological dataset for November, December, January, and February. This climatology provides a novel look at broad biochemical patterns that span roughly a half-century.